2018
DOI: 10.1007/s00704-018-2589-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the African greenbelt position on West African summer climate: a regional climate modeling study

Abstract: This modeling study is conducted to examine the potential impact of the reforestation (greenbelt) location (either in Sahel or in Guinean region) on West African summer climate system. To this end, three simulations using the regional climate model RegCM4 driven by ERA-Interim reanalysis were performed at 50 km horizontal resolution over a West African domain for the period 2000-2011. The first experiment, namely the control (CTRL), uses the standard vegetation cover, while the two others incorporate throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…We should note that, the assessments for the LST/SUBT effect here are likely affected by the models weaknesses/ errors. Additionally, it is worth pointing out that, this factor (LST/SUBT) as well as others elements such as SST , soil moisture (Xue et al 2004;Koster et al 2016;Saini et al 2016), vegetation (Xue et al 1996;Bamba et al 2018), and atmospheric internal variability Lee et al 2018) may have also contributed to the observed anomaly. Jee and Kim (2017) analyzed the influence of spin up time using the WRF version 3.6 on the simulation of heavy rainfall over Seoul and its adjacent cities.…”
Section: Domain Size and Boundary Locationmentioning
confidence: 99%
“…We should note that, the assessments for the LST/SUBT effect here are likely affected by the models weaknesses/ errors. Additionally, it is worth pointing out that, this factor (LST/SUBT) as well as others elements such as SST , soil moisture (Xue et al 2004;Koster et al 2016;Saini et al 2016), vegetation (Xue et al 1996;Bamba et al 2018), and atmospheric internal variability Lee et al 2018) may have also contributed to the observed anomaly. Jee and Kim (2017) analyzed the influence of spin up time using the WRF version 3.6 on the simulation of heavy rainfall over Seoul and its adjacent cities.…”
Section: Domain Size and Boundary Locationmentioning
confidence: 99%
“…More recently, there have been remarkable efforts to improve our understanding of the West African climate system using a regional climate modeling approach [28][29][30][31][32][33][34][35]. For instance, a number of projects have been developed to advance the understanding of the WAM system [31][32][33][34][35] and to comparatively assess the modeling of the WAM mean climatology and its projected changes [29,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…(), based on satellite observations, suggest a rapid regional intensification of Mesoscale Convective Systems (MCSs) whose potential drivers may include mineral aerosol concentrations and vegetation cover. Further investigations, using model‐based simulations, often indicate that reforestation/afforestation may increase the average rainfall and decrease mean temperature during summer season (Abiodun et al ., ; Hagos et al ., ; Bamba et al ., ), along with increasing (decreasing) the number of heatwave events over the reforested area (Sahel and Guinea coast) or causing a decrease (increase) of droughts occurrence over the Savanna and Guinea coast (Sahel) especially from July to September (Diasso and Abiodun, ; Odoulami et al ., ).…”
Section: Introductionmentioning
confidence: 99%